Complete removal of dentigerous cysts with preservation of associated teeth as an alternative to marsupialization in children and preadolescents - Hauer, Lukas; Seidlová, Petra; Merglová, Vlasta; Hrusak, Daniel; Böhmová, Hana; Posta, Petr; Gencur, Jiri; Netolicky, Jan (Journal of cranio-maxillofacial surgery, 2020)
The aim of this study is to evaluate the results of dentigerous cysts enucleation with preservation of cyst-associated teeth as a single procedure in a group of children and preadolescents. A retrospective case series of seven patients with 15 unerupted developing teeth associated with or adjacent to dentigerous cysts was conducted. Patients were treated using the uniform surgical protocol (cystectomy, preservation of cyst-associated teeth, without use of orthodontic traction, primary wound closure). The metric analysis of the cysts and unerupted teeth on CBCT and an evaluation of the state of involved teeth after the treatment was performed. The mean age of patients was 9.0 ± 2.1 years (range 5-12 years, median = 9 years). All teeth erupted spontaneously. No serious postoperative complications or recurrences of lesions were detected. The mean follow-up was 53.1 ± 15.7 months (range 25-71 months, median = 52 months). The cystectomy of dentigerous cysts with preservation of associated teeth may be considered an alternative to marsupialization in children and preadolescents.
Keywords: Neoplasm Recurrence, Local; Child; lidé; retrospektivní studie; dentigerózní cysta; Tooth, Unerupted; Dentigerous Cyst; dítě; předškolní dítě; neprořezané zuby; Retrospective Studies; Child, Preschool; lokální recidiva nádoru; Humans